Effectiveness of technology to support work based learning: the stakeholders’ perspective - Strachan , Rebecca; Liyanage , Lalith; Casselden , Biddy; Penlington , Roger (Research in Learning Technology, 2012)
Higher education provision typically requires learners to physically attend sessions on campus. The economic climate has changed significantly over the past few years in the UK and globally. Inevitably changes to student funding and the increased competitive nature of the job market have impacted on university teaching. The use of work based learning (WBL) is an alternative flexible form of learning that attempts to tackle these issues. It enables students to learn whilst they work, addressing the funding issues, and enhancing their employability through the acquisition of higher professional qualifications. Often such WBL programmes are designed, delivered and supported from the view of the student and academic staff with little consideration of other stakeholders such as employers, workplace mentors and professional bodies and the input they can bring to enrich the learning and teaching provision. This paper presents the findings from a survey conducted among stakeholders from all four pillars of WBL, namely the learner, the academic environment, the workplace and the external context. Online questionnaires and interviews were carried out with students, tutors, program leaders, employers and professional bodies from four postgraduate programmes at the university. The results show that while there is a reluctance to embrace technology among some academic staff, students are generally positive about using the technology. The survey also demonstrates that there is a lack of creativity and imagination in the use of technology, where often platforms such as virtual learning environments are used simply as repositories for presentation slides, handouts, etc. The results of the study conclude or rather remind all involving parties to pay more emphasis on quality of online programme delivery by embracing technology and use it in novel and imaginative ways to provide a learning and teaching provision fit for the twenty-first century. Keywords: work based learning; professional body; e-learning; distance learning; online learning